APLIKASI SPRAY DRYER UNTUK PENGERINGAN LARUTAN GARAM AMONIUM PERKLORAT SEBAGAI BAHAN PROPELAN - Cynthia Anggi Maulina; Ahdayani Rosarrah; Mohammad Djaeni (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Ammonium perchlorate ( AP ) is an  inorganic oxidizer that is widely used as a component of rocket propellants. In this research, spray drying was used to produce crystalline AP from  its saturated solution. A method of spray dryer is viscous liquid or paste contacted with thot air co-currently. Fluid is passed at a nozzle and came out into the form of fine granules ( droplet . Drying method was conducted to run4 variables change, such as the inlet temperature (80, 90, 100, 110, 120oC), flow rate air dryer (9,1 and 16.3 m/s), the material flow rate (5.5 and 5.8 ml/s) and material concentration (5, 10, 15, 20, 25% salt). The drying process lasts for 13 minutes and divided into 3 minutes of time spraying and 10 minutes for residence time in a spray dryer column.At a temperature of80° C, the concentration of20%, materialflow rateof 5.5ml/sand aair flow rate of9.1m /sobtainedsaltparticlediameterof67.144µmthen calculatesimilarityusingWebernumber, obtainedAPdiameter of42.79µm.While ata temperature of 100° C, the concentration of20%, with asame material and air flow rate,obtaineddriedsaltparticle diameterof23.433µm.Afterwards,similaritycalculationusing theWebernumberobtainedAPdiameter13.877µm. It can be seenthatthe result ofAPdiametersmaller than thediameter of theparticlesinLAPAN (National Aeronautics and Space Institute), rangedbetween100-170µm. We can conclude that the higher concentration of salt solution, then the diameter of products are also getting bigger. The higher temperature then the diameter of products are getting smaller. Calculation of similarity both ammonium perchlorate and salt with the weber number has the same graph trends.